A restorer‐of‐fertility‐like pentatricopeptide repeat protein promotes cytoplasmic male sterility in Arabidopsis thaliana. (26th November 2020) - Durand, Stéphanie; Ricou, Anthony; Simon, Matthieu; Dehaene, Noémie; Budar, Françoise; Camilleri, Christine
Summary: Pentatricopeptide repeat (PPR) proteins form a large family of proteins targeted to organelles, where they post‐transcriptionally modulate gene expression through binding to specific RNA sequences. Among them, the mitochondria‐targeted restorer‐of‐fertility (Rf) PPRs inhibit peculiar mitochondrial genes that are detrimental to male gametes and cause cytoplasmic male sterility (CMS). Here, we revealed three nuclear loci involved in CMS in a cross between two distant Arabidopsis thaliana strains, Sha and Cvi‐0. We identified the causal gene at one of these loci as RFL24, a conserved gene encoding a PPR protein related to known Rf PPRs. By analysing fertile revertants obtained in a male sterile background, we demonstrate that RFL24 promotes pollen abortion, in contrast with the previously described Rf PPRs, which allow pollen to survive in the presence of a sterilizing cytoplasm. We show that the sterility caused by the RFL24 Cvi‐0 allele results from higher expression of the gene during early pollen development. Finally, we predict a binding site for RFL24 upstream of two mitochondrial genes, the CMS gene and the important gene cob . These results suggest that the conservation of RFL24 is linked to a primary role of ensuring a proper functioning of mitochondria, and that it was subsequently diverted by the CMS gene to its benefit. Significance Statement: In cytoplasmic male sterility (CMS), pollen abortion is caused by mitochondrial genes, and fertility is restored by nuclear‐encoded proteins. Most identified restorers of fertility are pentatricopeptide repeat (PPR) proteins that suppress the mitochondrial sterilizing factors. Here, on the contrary, we report a restorer‐of‐fertility‐like PPR protein whose expression induces pollen death, revealing an unexpected role of PPRs in CMS.